NILAI-NILAI PENDIDIKAN KARAKTER DALAM PANDANGAN POLITIK SOEKARNO - I Nyoman Bayu Pramartha; Ni Putu Yuniarika Parwati (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The research aims to examine 1) Sukarno's political views 2) the values ​​of character education in Bung Karno's political views. This study uses historical research methods by prioritizing written sources that are relevant to the values ​​of character education in Bung Karno's political view. In this study using historical research methods. This research is literary because it analyzes from several book sources related to Bungkarno's political views and is associated with character education